Platform Merdeka Mengajar (PMM) untuk Meningkatkan Disiplin Positif Bagi Guru Penggerak di Mojokerto - Ardiantoro, Luki; Rudiyanto, M. Adik; Muslimin, Moh.; Ria S, Fitra (Fakultas Ekonomi Universitas Islam Majapahit, 2024)
The Merdeka Teaching Platform (PMM) was built to support the implementation of the Merdeka Curriculum so that it can help teachers get references, inspiration and understanding of the Merdeka Curriculum. This IT-based platform is also provided to be a driving partner for teachers and school principals in teaching, learning and creating. The Independent Curriculum is a strategic step in the context of changing the learning paradigm at the elementary, middle and high school levels. The most striking change is in the teaching curriculum which is centered on the needs of diverse students. Learning objectives are prepared by each educational unit with local content that has meaning given the environmental conditions. The goal to be achieved from this activity is the transformation of the 'classical' education process into meaningful and contextual education. In the framework of this change, adequate coaching abilities are needed from teachers and school principals, in order to be able to provide a more positive approach to students. The methods used in this activity are lectures and discussions, online training, in-house training in each educational unit through PMM, followed by a mentoring process over a period of 1 year, then full scale implementation in each educational unit.someone aims to help empower others by facilitating self-learning, personal growth and improvement. performance. The methods used in this activity are lectures and discussions, online training, in-house training in each educational unit, followed by a mentoring process over a period of 1 year, then full-scale implementation in each educational unit.